Franco-German leadership in the context of EU defence policy: From Brexit to the strategic compass - Ribeiro, I. M.; Rosa, J.; Xavier, A. I. (Journal of Contemporary European Studies, 2024)
Leadership is crucial for the success of a collective actor in reaching common goals. Its relevance is particularly visible in the EU, due to the difficulty in managing and converging a wide range of interests, especially in the intergovernmental field of defence. This article analyses Franco-German transactional leadership throughout the evolution of the EU’s security and defence policy, with a focus on the effects of Brexit. By highlighting the concept of leadership in international relations, this study identifies Franco-German actions and strategies within the Common Security and Defence Policy, reflecting on how these have shaped European defence and how Brexit changed existing dynamics. We conclude that France and Germany have led the EU’s security and defence project, albeit with limited success, with a shift towards a successful relaunch of EU defence in the aftermath of Brexit, aided by doubts over NATO and war in Ukraine. At the core of that limited success and representing the main obstacle lay diverging interests and strategies.